Early life factors and variation in adult kidney function in the Swedish LifeGene cohort - Agne Laucyte-Cibulskiene; Sara Hägg; Anders Christensson; Peter M. Nilsson (Scientific Reports)
Abstract Intrauterine fetal programming determines cardiorenal interaction later in life. We hypothesize that early life factors affect adult glomerular filtration rate and mean arterial pressure (MAP) directly or by interacting with postnatal growth trajectories. The population-based LifeGene study (Sweden) randomly recruited individuals aged 18 to 43 years (n = 12 167). They filled in a web-questionnaire and performed health tests (including bioimpedance measurements). Birth weight (BW), gestational age (GA), head circumference (HC), and birth length data were acquired from the Swedish Medical Birth Register. Postnatal growth was determined from BWz-scores and adult fat mass index. Creatinine and cystatin C-based kidney function were calculated (eGFRcr, eGFRcysC). After adjusting for sex, GA, adult age, and eGFRcr, a 1SD increase in BWz-score predicted a 1.15 mmHg increase in MAP. Meanwhile, every 1 cm decrease in HC was associated with an expected 0.29 mL/min/1.73m2 decrease in eGFRcr. Lower birth weight-to-placenta ratio was inversely related to eGFRcysC (p = 0.034). Postnatal down-regulation significantly affected a relatively lower eGFR but within normal range (p < 0.001). The postnatal catch-up did not affect kidney function. This study reveals the complex interrelationship between early life factors and adult kidney function that could be directly and indirectly influenced by adult body fat accumulation.